2008
DOI: 10.1111/j.1365-2249.2008.03809.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent low thymic activity and non-cardiac mortality in children with chromosome 22q11·2 microdeletion and partial DiGeorge syndrome

Abstract: SummaryA subgroup of patients with 22q11·2 microdeletion and partial DiGeorge syndrome (pDGS) appears to be susceptible to non-cardiac mortality (NCM) despite sufficient overall CD4 + T cells. To detect these patients, 20 newborns with 22q11·2 microdeletion and congenital heart disease were followed prospectively for 6 years. + T cell numbers were observed in 65%/75%, respectively, of patients in period A (< 1 year) declining to 22%/50%, respectively, of patients in period B (> 1/< 7 years). The percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Other authors have observed an increased risk of severe infections and autoimmune and lymphoproliferative complications in a specific immunologic subgroup of infants with 22q11DS. 39 Specific studies are needed to identify immunologic markers predictive of a higher risk for severe infections and autoimmune manifestations in patients with 22q11DS.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have observed an increased risk of severe infections and autoimmune and lymphoproliferative complications in a specific immunologic subgroup of infants with 22q11DS. 39 Specific studies are needed to identify immunologic markers predictive of a higher risk for severe infections and autoimmune manifestations in patients with 22q11DS.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting accounts regarding the gdTCR population with reductions and expansions reported [71,77]. A few patients with T lymphocytopenia appear to be at greater risk of significant viral or candidal infection or early infectious death, particularly those with a combined CD4 and CD8 lymphocytopenia and diminished thymic output, or associated hypoparathyroidism [78,79].…”
Section: Partial Combined Immunodeficiencymentioning
confidence: 99%
“…However, the majority of patients only display a partial cellular defect involving reductions in their T cell numbers and mild to moderate immunodeficiency without a predisposition to opportunistic infections such as recurrent candidiasis and/or severe viral infections. In contrast, some patients with 22q11.2DS suffer from fatal infectious diseases such as candidiasis (11), Pneumocystis jiroveci (12) or Epstein-Barr vi- rus infection (13). The occurrence of opportunistic infections is more common among patients with predisposing conditions that impair host defenses including being in an immunocompromised state.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present patient showed a normal CD4/CD8 ratio and a slightly decreased lymphocyte count, opportunistic infections should be taken into consideration. Patients with 22q11.2DS, might be associated with various immunologic abnormalities including elevated or decreased IgG levels, IgA deficiency, and a decreased B cell subset (12,13,16). Gennery et al (17) described that humoral immunodeficiency is more common than previously recognized in patients with 22q11.2DS, and 26 (81%) of their 32 22q11.2DS patients had severe or recurrent sinopulmonary infection.…”
Section: Discussionmentioning
confidence: 99%